Health Behaviors Based on an Active Lifestyle Among Generation Z: A Thematic Analysis - Azimi Nojadeh, Hamed; Abdavi, Fatemeh; Yurtsizoğlu, Zühal (International Journal of Sport Studies for Health, 2025)
The aim of the present study was to identify health behaviors based on an active lifestyle among Generation Z. This study was classified as applied and qualitative research. The method used in this study was Brown and Clark’s six-step thematic analysis. In order to achieve the desired goal, images and videos related to health behaviors, active lifestyle, and Generation Z that were available on the YouTube platform were extracted using Andy Search’s artificial intelligence. Then, articles published in the Scopus citation database that were in this field were extracted, and finally the top ten articles were identified using RStudio software. All of these items were analyzed and coded using Maxqda 2020 software, and finally eight themes for health behaviors and active lifestyle among Generation Z were identified. These themes included unhealthy behaviors and barriers, environmental and ethical issues, generational signs specific to Generation Z, mental and social health issues, the role of the environment and society, sports behaviors and physical activity, healthy eating and diet, and the role of technology and digital in health. Overall, the results of this research indicate that to promote an active lifestyle among Generation Z, strategies must be adopted that are consistent with the digital, social, and motivational characteristics of this generation.